International Agreements as a Basis for a Common Reaction of States Against Organized Crime (Kriminalističke teme, 2007)
Organized crime is one of the most serious security challenges in the Western Balkans region. It is a transnational issue that threatens to devalue civilization's heritage and foundations of a modern democratic society. Therefore, when confronting organized crime as a factor of instability among citizens, states resort to adequate forms of international cooperation. Passing and implementing international legal acts are a form of such cooperation, which is systematically presented in this document. Further on, authors note that, as for the implementation of international legal acts, it is necessary to have national legislation harmonized with new forms of fighting organized crime, and that law enforcement structures clearly implement all forms of international cooperation, especially at police and other law enforcement agencies' level. Therefore, the main task of the author of this document is to systematically present international legal acts that are crucial for the effective battle against organized crime.